¿Guerrilleros o campesinos? - Portela García, Juan Camilo (2024)
This article addresses the processes of interpretation in the public sphere about the 2013 National Agrarian Strike in Colombia, and especially the way in which the protesters were considered authentic and legitimate. Based on a cultural sociology approach, it argues that two symbolic processes contributed to the generation of social solidarity towards the peasantry during the strike. First, the transitional context derived from the peace talks between the government and the Revolutionary Armed Forces of Colombia (FARC) was discursively articulated in support of the protest. Second, there was a process of symbolic coalition around the idea of the peasant as a primordial and victimized identity that gathered the support of multiple social sectors. As a result of these processes, a codification of the strike and its protagonists as legitimate and authentic was positioned in the public sphere, eclipsing the warlike and antidemocratic classification of their motivations and actions. It is proposed that this case may contribute to illuminate some relevant aspects for the positioning of agrarian populism, especially in relation to the cultural dimension.